Richard Youngs (ed.): The European Union and Democracy Promotion: A Critical Global Assessment. (Czech Journal of International Relations, 2011)
Richard Youngs (ed.): The European Union and Democracy Promotion: A Critical Global Assessment. 1st ed. Baltimore: The Johns Hopkins University Press, 2010, 206 stran, ISBN-13: 978-0-8018-9732-0.